An implementation of natural language processing on ontology-based electronic health website: a case of female-related diseases domain - Handayani, Dini; Kartiwi, Mira; Hakim, S. (2010)
The advent of Internet has changed the way people live and search for information. Study showed that browsing on health information is amongst popular activities on the Internet, particularly among women. Despite a wide range of information one could gathered from the Internet, no website provides facility for the user to query the information using a natural language. It is the aim of this research to develop a prototype that allows individuals to query information from the web using natural language processing. This prototype will serve as a tool that allows both individuals and medical practitioners to refer and enquire to using natural language, and also enable them to share knowledge on Female-related diseases.